Innovations, technology and time allocation: Implications for labour productivity and welfare in Ghana - Felix Ankomah Asante; Martha Adimabuno Awo; Benjamin B. Bonzo; Ralph Sam; Sundus Saleemi (University of Bonn, Center for Development Research (ZEF), 2024)
This report investigates the dynamics of time allocation of men, women, and children in various types of work in rural households in Ghana. Using primary data and the Ghana Time Use Survey (GTUS) 2009, it examines gendered differences in time allocation and the interaction between income, various household types and time use. Moreover, women's time use patterns and their relationship to children's diets are analysed. We also assess patterns of time use and their relationship with productivity. Finally, domestic and agricultural technologies and time use patterns are assessed. The study finds persistent gender gaps, with women and girls disproportionately engaged in unpaid work across different household compositions and income groups. Household characteristics, such as singleadult households and income levels, shape time allocation, influencing the distribution of work among family members. Moreover, women's time on unpaid activities shows a positive association with children's dietary diversity, underscoring the importance of women's involvement in household chores and caregiving for nutritional outcomes. However, the study finds that women's time in unpaid work negatively impacts their labour productivity, suggesting potential trade-offs between domestic responsibilities and economic participation. Access to technologies and services, such as agricultural tools and markets, appears to play a role in shaping time use patterns and women's engagement in paid activities. The findings suggest policy implications for reducing the burden of unpaid work through technological interventions, redistributing household responsibilities, and promoting gender equality to enhance women's economic empowerment and household well-being.
Keywords: J22; J16; B54; 330; Time-Use; Unpaid Work; Gender Inequality; Children's Diets; Technology